Ukrainian insurance market and its positioning among the world's leading insurance markets - VOYNOVA, Evgeniia (Scientific journal «World of Finance», 2019)
Introduction.The insurance market is an important infrastructure component of highly developed economies, playing the role of an accumulator of money from the population and enterprises, and redistributing them through financial mechanisms to the real economy. Therefore, it is noteworthy to find out what the «ideal» insurance market is it and how this situation can be achieved in Ukraine.Purpose. The aim of the article is to analyze the criterion of determination the category “ideal” insurance market, to discover the Ukrainian insurance market and to identify how far the Ukrainian market from the ideal one.Results. Absolute indicators of the insurance industry development in Ukraine are very small in comparison with international indicators. The Ukrainian insurance market is integrated into the world one, and although it presents a limited range of insurance products, this is likely due to the small demand, which makes it irrational to implement more.Conclusion. The insurance market of Ukraine operates on a market basis, insurance companies meet the international standards and requirements of Ukrainian legislation. It is effective in terms of compliance with the current market conditions in Ukraine, but is far from perfect in terms of the potential of providing financial services to consumers and the use of accumulated insurance premiums in the financial system of the country.